Implementasi Kepemimpinan Dan Teknologi Informasi Komunikasi Dalam Lembaga Pendidikan - Wijayanti, Catur Lestari (Proceedings of Annual Conference on Community Engagement, 2022)
In the implementation of education, good leadership is needed, where information communication technology can be implemented by a leader so that the use and development of communication supported by information technology until the last two decades is increasing rapidly. This utilization not only serves as a supporting means to improve performance, but more than that it is the main means to win the increasingly competitive competition.This assistance uses a Participatory Action Research (PAR) approach, which prioritizes mastery of Information Communication Technology and the potential that exists around and possessed by a Leader. To then be used as an implementation material to empower the community, especially the educational environment itself. This PAR approach is very suitable to be applied in Educational Institutions in utilizing Mastery of Information Technology and existing potential to improve education.The results of the research are the implementation of leadership and communication information technology in educational institutions have a system both orally and in writing that is adapted to the ability and understanding of existing meanings and functions.  The development of this increasingly advanced education and inseparable from the development of science and technology that utilizes the development of information communication technology to be used in the educational process and other activities and utilizes existing technology for the learning process in the online system (online) and so on. So that new innovations will arise, by knowing and utilizing information communication technology, leadership performance will be better than before and help the management system in educational institutions because basically technology provides convenience and smoothness in the process.